Properties of Calcium Carbonate/Mica and Calcium Farbonate/Talc Filled Polypropylene Composites - Vincent, Sheril Rizal; Jaafar, Mariatti; Palaniandy, Samayamutthirian (Taylor's University, 2014)
Mineral fillers namely talc, calcium carbonate, mica, glass and carbon fibres are common fillers used in plastic industry that can alter thermoplastic properties. With the incorporation of fillers, significant outcome can be observed especially in the mechanical properties of polymer composites produced apart from its rigidity and resistance to temperature. Properties of single and hybrid fillers filled polypropylene (PP) composites were studied in this research work. Mineral fillers such as talc, mica and calcium carbonate (CaCO3) were incorporated into PP composites. Realising the advantage of each mineral filler and the effect of hybrid fillers, CaCO3/Talc (CC/T) and CaCO3/Mica (CC/M) at 40 wt% were investigated. Generally, the results demonstrated that CC/M has higher tensile modulus than CC/T and both hybrids composites did not give significant effect on the tensile strength. Thermogravimetric analysis (TGA) results revealed that CC/M increased thermal stability of PP composites when compared to CC/T. Flammability testing on PP hybrid composites was carried out where lower burning rate indicates better flammability. From the results, it shows that CC/M system have better flammability compared to CC/T system.